(untitled) (Journal of National Institute of Ophthalmology, 2023)
Purpose: To study the clinical profile & visual outcome of ocular chemical injuries. Methods: This observational retrospective study was performed on 50 patients with chemical injuries attending in cornea clinic from January 2022 to December 2022 in a tertiary Eye Institute & Hospital in Bangladesh. A detailed history of the patients and history of presenting complaints was taken. An ocular examination was performed. Visual acuity was recorded by using Snellen’s test-type Chart. A thorough examination was carried out on slit-lamp, direct & indirect ophthalmoscopes. Clinical grading was done by Roper Hall Classification. Other’s ocular investigations were done when required. Results: In the present study, 50 patients were included of which 60% (30) were male and 40% (20) were females. In the present study, 11-20 years of age patients are 18(36%) & 0-10 years of age are 12(24%).Most of the cases were day labor 16(32%), followed by students12( 24%) ,housewife 4(8%) & others are 18 (36%). As per the Roper Hall Classification, most of the eyes sustained grade II chemical injury at 36% (30 eyes); followed by grade IV at 26%: grade III was 20%, and grade I was 18%. The visual acuity at presentation, 17(34%) patients had visual acuity 6/12- 6/24. On the other hand, 14(28%) have a counting finger. Visual acuity at the final follow-up, 19(38%) patients had visual acuity 6/12- 6/24. On the other hand, 16(32%) had a counting finger. The management of chemical injury, AMG + BCL was done on 54% of patients & conservative management was done on 32% of patients. Conclusion: The incidence was more in the younger working population, with a majority of injuries occurring in less than 30 years of age. The severity of chemical burn belonging to grade II and grade IV injuries. Henceforth the visual outcome was better and complications were much less after immediate management. Saline wash & Amniotic membrane Grafting(AMG) with fresh amniotic membrane increases patient comfort and reduces inflammation. Public health initiatives are critical to prevent chemical injuries in mitigating the poor visual prognosis. J.Natl.Inst.Ophthalmol.2023;6(1): 27-31